Synthesis, Characterization, and Catalytic Performance of H₃[α-PMo₁₂O₄₀]·nH₂O-TiO₂ in Cyclohexane Oxidation - Lingga, Fitra Wahyuni; Jefri, Jefri; Mohadi, Risfidian; Lesbani, Aldes (Indonesian Journal of Material Research, 2025)
This study aims to synthesize and characterize the H₃[α-PMo₁₂O₄₀].nH₂O-TiO₂ composite as a heterogeneous catalyst for cyclohexane oxidation using H₂O₂. FT-IR and XRD characterization showed the interaction between POM and TiO₂, with an increase in TiO₂ ratio leading to a decrease in POM crystallinity. Reaction optimization showed that the POM-1.00TiO₂ catalyst gave the highest conversion of 99.95% at 80°C, 2 hours reaction time, 3 mL H₂O₂ volume, and 0.1 g catalyst mass. GC analysis confirmed the formation of cyclohexanol and cyclohexanone, with the optimized conditions resulting in a balanced selectivity of 35.51% for cyclohexanol and 34.69% for cyclohexanone, demonstrating the catalyst's effectiveness in cyclohexane oxidation.